2019
DOI: 10.1177/0950422218824507
|View full text |Cite
|
Sign up to set email alerts
|

Didactic games as student-friendly tools for learning hydraulics in a technical university’s undergraduate curriculum

Abstract: This article reports research into the didactic processes of a creative gamified learning process for hydraulics in an undergraduate technical university curriculum, enhanced by industry collaboration. It is based on the use of educational theories of didactic transposition, competency building, learning gamification and emotional intelligence. It is shown that improvement in a student’s motivation with regard to the creative learning of hydraulics in an undergraduate curriculum can be achieved throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…The proportion of recreational videogame players among students has steadily increased over time (Prensky, 2001) and this population is expected to find interactive, openended instruction more resonant with their learning style than the classical methods based on unilateral expositions of information. A number of successfully implemented instructional methods incorporating games serves as a testimony to the actuality of interactive, inherently playful education (Gorgen et al, 2020;Liuta et al, 2019;Veldkamp et al, 2020), especially for today's student cohorts heavily influenced by the videogame culture.…”
Section: Results Of the Surveysmentioning
confidence: 99%
“…The proportion of recreational videogame players among students has steadily increased over time (Prensky, 2001) and this population is expected to find interactive, openended instruction more resonant with their learning style than the classical methods based on unilateral expositions of information. A number of successfully implemented instructional methods incorporating games serves as a testimony to the actuality of interactive, inherently playful education (Gorgen et al, 2020;Liuta et al, 2019;Veldkamp et al, 2020), especially for today's student cohorts heavily influenced by the videogame culture.…”
Section: Results Of the Surveysmentioning
confidence: 99%
“…Experts empirically record that in the higher education system, teachers are limited mainly to the creation and use of role-playing games in the educational process [12,32]. This use of didactic games is ineffective for the professional training of studentsfuture bachelors of psychological and pedagogical education [20,35]. As shown, the experiment, which was developed and implemented outside the classroom on the basis of students 'self-management, a special set of didactic games turned out to be reliably (p<0.05) effective for increasing students' legal literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the form of activity and impact, didactic games used in the process of professional training are divided into digital games on mobile devices and computers [19] and classroom games with direct contact interaction of participants [13,20]. Experts, based on empirical research, prove the effectiveness of digital gamification through the creation of a creative and free way of thinking that encourages students to try new things and not be afraid of gaming failures in the learning process [21].…”
Section: Gamification In Learningmentioning
confidence: 99%
“…49,50 The employment of "paper&pencil" didactic games can be successful in terms of understanding and cognition processes, as proven in hydraulic courses. 51 Assessment methods. An interesting non-assessment practical intervention in a secondyear fluid mechanics course was reported by McClelland Pott et al 52 The authors confirmed that non-assessment-driven learning reduced student perceptions of workload, anxiety, and time pressure, and assessment proved unnecessary to drive or enforce learning.…”
Section: Fluid Mechanics Educationmentioning
confidence: 99%